Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/1380485
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA–mRNA Expression Patterns in Invasive Pituitary Adenomas: A Microarray Analysis

Abstract: Background. Long noncoding RNAs (lncRNAs) play important roles in the tumorigenesis and progression of various cancer types; however, their roles in the development of invasive pituitary adenomas (PAs) remain to be investigated. Methods. lncRNA microarray analysis was performed for three invasive and three noninvasive PAs. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed, and coexpression networks between lncRNA and mRNA were constructed. Furthermore, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…miRNAs are small protein non-coding RNAs that regulate gene expression post-transcriptionally, and their abnormal expression has been associated with progress of PAs 9 . Divergent lncRNAs have been found in invasive PAs 10 , and different miRNAs are overexpressed in the three PA clusters. The ACTH adenoma group overexpresses miR4501; CNFPA upregulates miR582, miR4774, and LINC01351 ; while the GH, TSH, and PRL adenoma cluster overexpresses miR377 and miR136 5 .…”
Section: Advances In Understanding and Managing Pituitary Adenomasmentioning
confidence: 97%
“…miRNAs are small protein non-coding RNAs that regulate gene expression post-transcriptionally, and their abnormal expression has been associated with progress of PAs 9 . Divergent lncRNAs have been found in invasive PAs 10 , and different miRNAs are overexpressed in the three PA clusters. The ACTH adenoma group overexpresses miR4501; CNFPA upregulates miR582, miR4774, and LINC01351 ; while the GH, TSH, and PRL adenoma cluster overexpresses miR377 and miR136 5 .…”
Section: Advances In Understanding and Managing Pituitary Adenomasmentioning
confidence: 97%
“…53 Among them, two lncRNAs, FAM182B and LOC105375785, were found to be involved in the invasiveness of PA and might serve as promising candidate biomarkers for the diagnosis of IPAs. 53 Another transcriptome sequencing study found 70 differentially expressed lncRNAs between invasive and noninvasive GH-PAs, wherein epithelial cell differentiation and development pathways were restrained in invasive GH-PAs by functional annotations and enrichment analysis. 54 Decreased expression of lncRNA SPINT1-AS1 was suggested to serve as an indicator of invasive GH-PAs independent of the unfavorable prognosis.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…The most significantly DE lncRNA, n334366, is a unique satellite in the co-expression network, where it is related to the neuroactive ligand–receptor interaction pathways [ 84 ]. Subsequently, a total of 246 DE lncRNAs were identified between IPA and NIPA using a lncRNA microarray analysis [ 85 ]. The LOC105371531, LOC105375785, and FAM182B expression levels were significantly decreased in IPA compared to NIPA according to qRT-PCR [ 85 ].…”
Section: Lncrna and Pamentioning
confidence: 99%
“…Subsequently, a total of 246 DE lncRNAs were identified between IPA and NIPA using a lncRNA microarray analysis [ 85 ]. The LOC105371531, LOC105375785, and FAM182B expression levels were significantly decreased in IPA compared to NIPA according to qRT-PCR [ 85 ]. ROC curve analysis showed that the expression of LOC105375785 and FAM182B could distinguish IPA from NIPA, suggesting that LOC105375785 and FAM182B might be implicated in the invasiveness of IPAs and might be novel biomarkers for the diagnosis of IPAs.…”
Section: Lncrna and Pamentioning
confidence: 99%
See 1 more Smart Citation